Meningkatkan Kemampuan Bahasa Anak Usia Dini melalui Pembelajaran Multimedia Interaktif Berbasis AR dan VR - Wulandari, Fitrianti; Widyaningrum, Novita; Sa’ida, Naili; Masturoh, Umi (Academicus: Journal of Teaching and Learning, 2025)
This study aims to evaluate the effectiveness of the use of interactive multimedia based on Augmented Reality (AR) and Virtual Reality (VR) in improving early childhood language skills. This study uses a quantitative approach with a quasi-experimental nonequivalent control group design. The study subjects consisted of two groups, namely the experimental class using AR/VR media and the control class using conventional picture story media. The participants were 20 children at Miftahul Ulum Kindergarten, 10 children in each group. The research instrument was a language ability test given before (pre-test) and after (post-test) the treatment. The data were analysed using descriptive and inferential statistics, including normality, homogeneity, and t-test tests at a significance level of 0.05. The analysis showed that the experimental class's average post-test score was 67.1 points higher than the control class's average of 62.4. The t-test showed that t count 0.998 was greater than t table 0.444, which means there was a significant difference between the two groups. These findings indicate that interactive multimedia based on AR and VR can provide a more enjoyable and meaningful learning experience and effectively improve early childhood language skills. This study recommends integrating immersive technology in PAUD learning as an innovative effort to optimally support children's language development.